Mental health counseling for patients undergoing chemotherapy - Anwar, Irawati; Yunus, Suwarda; Iwan, Iwan (CV. Paperhome Indonesia, 2025)
Malignant disease with chemotherapy is the highest incidence of disease in the world, the treatment that patients go through makes them worried and anxiety, this occurs by itself and affects the patient's immune system. This anxiety requires support and mental strengthening from both the family and health service providers. Counseling or education is needed for patients and families to increase the effectiveness of the patient's mental health. Family support helps improve physical health and also psychological health. So that the side effects of chemotherapy can be minimized, and there will be changes in behavior and increase patient compliance with treatment.